Tailoring Properties of Hafnium Nitride Thin Film via Reactive Gas-Timing RF Magnetron Sputtering for Surface Enhanced-Raman Scattering Substrates - Nguentra Sucheewa; Winadda Wongwiriyapan; Annop Klamchuen; Michiko Obata; Masatsugu Fujishige; Kenji Takeuchi; Tossaporn Lertvanithphol; Tuksadon Wutikhun; Saifon Kullyakool; Wanwalee Auttasiri; Nataporn Sowasod; Theerayut Prataen; et al. (My University, 2022)
This study successfully demonstrated the tailoring properties of hafnium nitride (HfN) thin films via reactive gas-timing (RGT) RF magnetron sputtering for surface-enhanced Raman spectroscopy (SERS) substrate applications. The optimal RGT sputtering condition was investigated by varying the duration time of the argon and nitrogen gas sequence. The RGT technique formed thin films with a grain size of approximately 15 nm. Additionally, the atomic ratios of nitrogen and hafnium can be controlled between 0.24 and 0.28, which is greater than the conventional technique, resulting in a high absorbance in the long wavelength region. Moreover, the HfN thin film exhibited a high Raman signal intensity with an EF of 8.5 × 104 to methylene blue molecules and was capable of being reused five times. A superior performance of HfN as a SERS substrate can be attributed to its tailored grain size and chemical composition, which results in an increase in the hot spot effect. These results demonstrate that the RGT technique is a viable method for fabricating HfN thin films with controlled properties at room temperature, which makes them an attractive material for SERS and other plasmonic applications.
Keywords: Hafnium; Gold and Silver Nanoparticles Synthesis and Applications